IMPLEMENTING THE THEORY OF TSAMAN IN RUBBER’S PRICING STANDARD IN INDRA MAKMUR DISTRICT, ACEH PROVINCE, INDONESIA - Mizal Helmi; Mukhsin Nyak Umar (JURISTA: Jurnal Hukum dan Keadilan, 2025)
The rubber trade in Indra Makmur District, East Aceh Regency, is a primary source of income for local farmers. However, the price determination by middlemen often leads to injustice and a lack of transparency, particularly regarding the relationship between rubber quality and selling price. This study aims to analyze the relationship between rubber quality and price determination from the perspective of tsaman according to Islamic fiqh muamalah. A qualitative descriptive method was employed, with data collected through interviews, observations, and documentation. The findings indicate that although factors such as moisture content, color, and latex content affect the price, the price-setting process often lacks transparency and tends to disadvantage farmers. From the tsaman perspective, current pricing practices do not fully comply with the principles of justice, clarity, and openness in sales contracts. This study recommends the application of Sharia values in rubber trading to create a fairer and more sustainable pricing system for both farmers and middlemen.